Antitumour effect of Lactobacillus casei CRL 431 on different experimental tumours - Bibas Bonet, María Eugenia (2005)
We analysed the mechanisms of tumour inhibition by Lactobacillus casei CRL 431 orally administered, for fibrosarcome (non intestinal tumour, NIT) and for carcinoma (intestinal tumour, IT), both induced chemically. Balb/c mice were fed with L. casei (1.2 × 109 cel/day/ mouse) for two consecutive days previous to the induction of the respective tumours. After IT induction, oral administration of L. casei was repeated cyclically every 5 days for 5 months. In order to determine the percentage of tumour inhibition in the NIT mice, morphometric studies were performed and TNFα levels in serum and spleen cells were determined. In the IT, macroscopic and histopathological studies were performed and the number of intestinal IgA+ and TNFα+ cells was determined. We demonstrated that L. casei CRL 431 inhibited the growth of both tumours. In the case of NIT animals treated with L. casei, the high levels of serum TNFα would play an important role in the inhibition of tumour growth due to its cytolytic activity against tumour cells. In the IT, the increase in IgA+ and TNFα+ cells could be involved in the inhibitory effect observed. Our results showed that the selection of the probiotic bacteria with antitumour activity would not be limited to the determination of the cytokines relevant to this activity because of the multifactorial etiology of the different cancers.